The Qur’anic Word “al-bayān” in (Q. 55:4) and its Semantic Correlation with the Human Faculty of Speech; A Comparative study of Sunni and Shi’ite Exegetes’ Viewpoints - Ahmad Karimi; Firua Aslani-Alavar (پژوهش‌های تفسیر تطبیقی, 2021)
Received: 2021/1/18  |   Accepted: 2021/5/22A survey of Qur’anic exegetes reveals that they have five main viewpoints on the meaning of the word “al-bayān” in (Q. 55:4). Some consider it to mean the human faculty of speech, some to the expression of everything, some to the human faculty of reason, some to the names of objects and creatures, and some to the Holy Qur’an itself. Given the mentioned differences concerning the meaning of the Qur’anic word “al-bayān”, as well as the lack of independent research in this regard, the present article attempts to analyze its true meaning, seeking a suitable connection with the context of the verse in question. According to the achievements, the opinion of those Qur’anic exegetes, either Sunni or Shi’ite, who consider “al-bayān” in a semantic correlation with the meaning of human faculty of speech seems more satisfactory, comprehensive, and convincing. It should be pointed out that the first meaning of the word that comes to mind from observing the context of the verses is “speech”. In the same way, there is exact evidence in earlier literary, historical, and narrative texts that illustrate the application of the Arabic word “bayān” in the meaning of speech. Furthermore, according to (Q. 14:4), the Qur’an attributes the human faculty of explanation to language. On the other hand, it should not be neglected that God Almighty has called the Qur’an a general expression for the people. Since the material and apparent nature of the Qur’an at the time of its revelation was nothing but the nature of speech and language, it becomes clear that the meaning of "al-bayān" is speech. Seemingly, the other meanings mentioned by the Qur’anic exegetes for the word in question seem somehow related to language and the human faculty of speech.Karimi, A; Aslani-Alavar, F. (2022) The Qur’anic Word “al-bayān” in (Q. 55:4) and its Semantic Correlation with the Human Faculty of Speech; A Comparative study of Sunni and Shi’ite Exegetes’ Viewpoints. Biannual Journal of Comparative Exegetical Researches, 7 (14) 271-291. Doi: 22091/PTT.2021.6121.1857.